Google Translate in EFL Freshmen’s Writing Assignments: Uses, Awareness of Benefits and Drawbacks, and Perceived Reliance - Timotius Pradana A. Moelyono; Elisabet Titik Murtisari; Daniel Kurniawan; Andrew Thren (Vision: Journal for Language and Foreign Language Learning, 2023)
Although technology use is inevitable among language learners, using Machine Translation (MT), such as Google Translate (GT), remains controversial in language learning. Despite its advances, it may be detrimental to L2 learning when used excessively, especially for those with more limited linguistic resources. This research investigates first-year EFL students' autonomous utilization of GT in writing assignments, explores their awareness of GT’s advantages and disadvantages, and assesses their perceived relative reliance on the technology. As many as 85 Indonesian EFL first-year students participated in this study by completing questionnaires consisting of closed-ended and open-ended questions. Even though most students recognized GT’s potential negative impact on language learning, this study reveals how various factors have contributed to its notably significant usage among them. While most participants reported using GT only occasionally and mainly at the word level, their use for translating longer texts was significantly higher than in previous research involving students at different English competence levels. Additionally, boosting confidence, convenience, and serving as language scaffolding were identified as GT’s main benefits, leading to students’ reliance on technology. Most expressed potential difficulty working without GT. Recommendations were made to support less-proficient students, given the growing prevalence of MT in language education.